RCCB's nuisance tripping at final distribution boards MIMOS as a case study / Jailani Muda - Muda, Jailani (1999)
Power quality becomes a major concern of both electricity providers and their users. For the users, the economie impact of power disturbances can range from several hundred dollars to repair or replace home appliances to millions of dollars in product or production losses and cleanup. For utilities, system disturbances can tead to user dissatisfaction and revenue losses. Many have concluded that the problems are caused by power supplier (i.e. Tenaga Nasional Berhad), but the main reason to the power quality problems is increment of nonlinear loads in the particular system. Wiring installation and grounding practice in the distribution system can also contribute to these problems. Therefore, as a user serious attention have to be given in wiring and grounding installation to make sure that the equipment runctions as desires. This project mainly focused on the effects of poor or improper grounding, inadequate wiring installation practice and high content of harmonie in the distribution systems that cause power quality problems. The aim of this project is to understand the avaiiable theory and correlation with the actual cases referring to Residual Current Circuit Breakers (RCCB's) nuisance trippings at Institut Sistem Mikroelektronik Malaysia (MIMOS) as a case study. A visual inspection was done to know the existing wiring and grounding practice at the MIMOS buildings. Data analysis of voltage and current events was monitored using Reliable Power Meter (RPM) has been made to assist analysis and problem's diagnosis. Inadequate wiring, improper grounding and high harmonie content presence causes problem and failure to the operation of the equipment, due to protection device tripping are discussed together with the recommended solutions.